Sami Food Practices and Traditional Ecological Knowledge - Casi, Corinna (Sustainable governance and management of food systems, 2019)
This paper focuses on Sami Indigenous Peoples’ food system as an example to consider for alternative solutions, which do not put stress on the planet ecosystems. Their food system is linked with Sami traditional ecological knowledge and livelihood practices, and all together they inform the Sami’s worldview. Furthermore, I suggest that Sami traditional food system represents a model of ‘sustainable food production and consumption’ to look at in order to foster a higher respect for the food we eat and diminish the current food waste. I call the Sami food system ‘sustainable’ due to their bond to the food production, harvesting and processing and to the high respect of the natural environment and the natural cycle of animals and plants. The Aristotelian philosophical tradition and its virtue ethics help to identify a 'Sami sustainability virtue'. This is understood as a practical wisdom of Sami Indigenous People based on their worldview and traditional ecological knowledge.